An Exploratory Analysis of the Number of Corruption Crimes in Romania from 2014 to 2020 - Florea, Iulia Oana; Aivaz, Kamer Ainur (Technium Social Sciences Journal, 2022)
Corruption is a form of dishonesty or a crime that is undertaken by a person or organization entrusted with a position of authority to gain illicit benefits or abuse power for personal gain. Corruption can involve many activities that include bribery, influence peddling and embezzlement and can also involve practices that are legal in many countries. There is a consensus regarding the presence of this phenomenon since ancient times, but this consensus is not maintained regarding the definition or motivation of this phenomenon. The objectives of this paper are to highlight the dynamics of different types of corruption crimes that occurred between 2014 and 2020 in Romania which may help the law enforcement agencies in the fight against corruption. The methodology used for this paper is principal component analysis.